The nexus between data analytics and firm performance - Raazia Gul; Nazima Ellahi (Cogent Business & Management, 2021)
The increased access and availability of information technology solutions have brought structural shifts in traditional business models, processes, and activities worldwide. As a result, the innovative ways of doing business and practices have disrupted the traditional businesses and technologies. This study investigates the impact of investment in data analytics on the financial performance of banks in Pakistan. A sample of 32 banks including commercial and microfinance banks for 2010 to 2019 was selected. Random effect panel estimation and instrumental variable two-stage least square were employed to quantify the impact of data analytics on firm performance. The results indicate that investment in data analytics increases the productivity of banks by 10%. However, the impact of investment in DA on profitability measures including return on assets, return on equity, and net interest income was negative, reflecting the "profitability paradox." In the current era of digitalization, the banks need to invest in innovative technologies which have analytical capabilities to remain competitive and sustainable.
Keywords: 650; Data analytics; Digitalization; financial sector; productivity; financialperformance